The antibacterial activity of "Satureja hortensis" extract and essential oil against oral bacteria - Leila Golpasand Hagh; Atefe Arefian; Ahmad Farajzade; Sana Dibazar; Neda Samiea (Wolters Kluwer Medknow Publications, 2019)
Background: Recently, there has been an increasing growth in research on medical plant's effect on dental plaque bacteria. The aim of this study was to determine the antibacterial effects of Satureja hortensis extract and its essential oil (EO) on Streptococcus salivarius, Streptococcus sanguis, and Streptococcus mutans as important bacteria in early supragingival dental plaque formation. Materials and Methods: In this in vitro study, different concentrations of S. hortensis extract and its EO were prepared using double dilution method. The disc diffusion method was used to determine antibacterial activity. Based on these measurements, the minimal inhibitory concentration value was reported for each bacterium. Antibiotics used as positive controls in this study were erythromycin (15 μg) and tetracycline (30 μg). t-test and ANOVA were used for statistical analysis (P < 0.05). Results: Aqueous and methanolic extract did not show significant antibacterial activity, but the EO significantly inhibited the growth of the test bacteria compared to positive control (P < 0.05). High concentrations of EO processed greater antimicrobial effects against three oral bacteria than other low concentrations (P < 0.0001). For S. mutans, the inhibition effect of tetracycline 30 μg was similar with 50% (P = 0.789) and 25% (P = 0.158) dosages of the EO. For S. salivarius, the effect of tetracycline 30 μg was similar to 50% dosages of the EO (P = 0.122). For S. sanguis, the effect of erythromycin 15 μg was lower than 50% (P = 0.0006) and 25% (P = 0.003) dosages of the EO. The inhibition effects of all concentrations of EO were higher for S. sanguis. S. salivarius and S. sanguis are more sensitive than S. mutans to S. hortensis EO. Conclusion: Due to the strong antibacterial effect of S. hortensis EO on the oral bacteria growth, it can be served as herbal mouth rinse, while to confirm this antibacterial effect, further clinical studies are necessary.